Clinical profile of diabetic ketoacidosis in adults - Rao, V D; Pradhan, B; Mallikarjuna, Y; Reddy, R (Health Renaissance, 2012)
Introduction: Diabetic ketoacidosis (DKA) is a potentially life-threatening complication of diabetes mellitus. Recent epidemiological studies indicate that hospitalizations for DKA in the U.S. are increasing. Epidemiological studies from India are limited. We undertook this observational study to analyse the clinical profiles of DKA in adults in south India. Methods: This study was conducted in at a tertiary care center in Andhra Pradesh for one year from Aug 2010 to July 2011. Diagnosis of DKA was made by the presence of (1) Plasma glucose level of 250mg/dl or higher (2) Serum bicarbonate level of 15mEq/lt or lower (3) Arterial blood pH of 7.3 or lower or a venous blood pH of 7.25 or lower (4) Presence of moderate or large urine ketones. All the patients were treated with institutional treatment protocol. Results: Of 27 patients, 22(81%) had type2 diabetes and 5(19%) had type 1 DM .10 were females and 17 males. Age of the patients ranged between 18 to 70 years, with an average of 45.3 years. Precipitating factors were present in 60% of the admissions. Non-compliance or discontinuation of drug therapy was seen in fifty per cent of patients. Average length of hospital stay was slightly longer in type 1 than type 2 DM patients Conclusion: A significant proportion of DKA occurs in patients with type 2 diabetes and many of these cases can be prevented with proper patient education and effective communication with a health care provider during an inter-current illness. DOI: http://dx.doi.org/10.3126/hren.v10i2.6569 Health Renaissance 2012; Vol 10 (No.2); 80-86